G-jitter fully developed heat and mass transfer by mixed convection flow between two parallel plates with constant heat flux - Wan Nor Zaleha Amin,; Ahmad Qushairi Mohammad,; Sharidan Shafie,; Muhammad Qasim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
In this research, the problem of heat and mass transfer in mixed convection flow induced by g-jitter is studied analytically. The flow passes through an infinite length of vertical parallel plates. The left wall of the plate is prescribed with constant heat flux while the right wall is maintained at a constant temperature. The governing boundary layer equations are transformed into dimensionless equations by using the appropriate dimensionless variables. The behaviors of the velocity, temperature, and concentration profiles of the fluid are analyzed by Fourier method and illustrated graphically as well. Results show that due to an increase in value of wall temperature, the fluid temperature increases. It is found that the controlling parameters strongly affect the heat and mass transfer characteristics in g-jitter fluid flow.